Leaving no one behind : building resilience for food security in a period of health emergency (2022)
The reading of this article is structured firstly in a vision on pandemics and rights, through a historical link developer of social rights, emphasizing the right to food, food security, and food sovereignty linked by the item of the theme, respect for human rights, to achieve the well-being of people. Methods, synthesis, and explanatory analysis were used, with the aim of systematizing the need to reaffirm a series of principles, obligations, projections that States must assume to achieve the sustainable objectives of the 2030 Agenda in times of health emergency, a product to covid-19. This framework defends the idea that agri-food policies should be aimed at adequate and safe food as a human right, reorganized by a governance system that creates innovative spaces for participation aimed at all citizens, so that no one is left behind.